Computational fluid dynamics simulations to improve performance characteristics of a manifold having a central inlet and outlet - Ganguli, Arijit A.; Pandit, Aniruddha B. (Frontiers in Energy Research, 2022)
In the present work, performance/flow characteristics (namely, the effect of operating parameters like pressure on flow patterns, pressure drop, and the extent of flow uniformity) and transport phenomena of a manifold (header tube assembly) having an inlet and outlet at the center are carried out on a macroscale geometry using CFD simulations. In this study, an existing design available in the published literature (with high flow non-uniformity) was considered and an optimized design (with minimum flow non-uniformity) was developed. The optimization is performed by incorporating a perforated plate (distributor) inside the top header of the manifold. First, CFD simulations for different configurations of the existing design with the perforated plate have been performed for a pressure of 10 bar with steam as a working fluid, and an optimized configuration having a minimum flow non-uniformity of less than 3% is obtained. CFD simulations for both the existing design and optimized design are then performed for a pressure range (10 ≤ p ≤ 70 bar) and the corresponding Reynolds number (Re) range (2.82E+05 ≤ Re ≤ 2.82E+06) with steam as the working fluid. The extent of non-uniformity (ENU) and pressure drop for the existing design (without a distributor) and optimized design (with a distributor) have been analyzed and compared. The optimized design gives the near uniform flow (∼1–4%) for all pressures and Reynolds numbers considered. An empirical correlation relating the friction factor (as per the Chilton–Colburn analogy) and Re has been developed for both designs (with and without a distributor). The predicted friction factors are compared with the present CFD predictions, and experimental data of the shell and tube heat exchanger are available in the published literature. A good agreement within a 10–15% deviation has been observed. Based on the Chilton–Colburn analogy, a correlation for the Nusselt number is obtained from the friction factor correlations for both with and without distributor cases. The correlations for friction factors were found to be valid under any operating conditions for a pressure drop range within 0.05 < ∆p < 1.8 bar irrespective of the design of the distributor, assuming that the manifold is able to withstand the pressure drops in the given range.